The Depression Anxiety Stress Scale 8-Items Expresses Robust Psychometric Properties as an Ideal Shorter Version of the Depression Anxiety Stress Scale 21 Among Healthy Respondents From Three Continents - Ali, Amira Mohammed; Hori, Hiroaki; Kim, Yoshiharu; Kunugi, Hiroshi (Frontiers in Psychology, 2022)
To examine the cultural limitations and implications in the applicability of the Depression Anxiety Stress Scale 8-items (DASS-8)—a shortened version of the DASS-21 recently introduced in an Arab sample—this study evaluated its psychometric properties, including measurement invariance, among healthy subjects from the United States, Australia, and Ghana. Confirmatory factor analysis revealed good fit of the DASS-8 relative to a 12-item version (DASS-12). Both the DASS-8 and the DASS-12 were invariant at all levels across genders, employment status, and students vs non-students. The DASS-8/DASS-12 also held invariance at the configural and metric levels across all countries, albeit scalar invariance was not maintained due to misspecification of the factor loadings in the Ghanian sample. Mann Whitney test revealed significantly lower levels of mental symptomatology on the DASS measures among Ghanian students than English-speaking respondents (both students and non-students). The DASS-8 expressed excellent internal consistency (coefficient alpha = 0.89), good convergent validity—noted by high values of item-total correlations (r = 0.87 to 0.88), good predictive validity—indicated by significantly strong correlation with the DASS-21 and its subscales (r = 0.95 to 0.80), and adequate discriminant validity—indicated by heterotrait-monotrait ratio of correlations < 0.85. The DASS-8 correlated with the Internet Gaming Disorder-9, the Adult attention-deficit/hyperactivity disorder Self-Report Scale, and the Individualism and Collectivism Scale / Culture Orientation Scale at the same level as the DASS-21 and the DASS-12, denoting its adequate criterion validity. The DASS-8 can be used as a brief alternative to the DASS-21 to screen for mental symptomatology in English-speaking and African cultures. However, the same scores on the DASS-8 and the DASS-12 may not always indicate the same level of symptom severity in subjects from different countries. Further inter-cultural evaluations of the DASS-8 are needed.